UJI VIABILITAS DAN VIGORITAS BENIH PADI LOKAL RAMOS ADAPTIF DELI SERDANG DENGAN BERBAGAI TINGKAT DOSIS IRRADIASI SINAR GAMMA DI PERSEMAIAN - Sri Utami (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This research to know the influence of various a dose of irradiasi gamma rays against viabilitas and vigoritas seeds and to knows the difference the growth of seedlings of the paddy resulting from irradiasi gamma rays in the seddbed. The research done on October to December 2011 in Kebun Percobaan the faculty of agriculture UMSU in Jln. Tuar Kelurahan Medan Amplas, Kecamatan Denai, Kotamadya Medan.  The research using random complete non factorials consist of three different levels of  dose  irradiasi (D) ie: D0= 0 Gy (kontrol),  D1= 100 Gy, D2  = 200 Gy, D3= 300 Gy, D4= 400 Gy, D5= 500 Gy. Irradiasi gamma rays on seeds cause a decrease in viabilitas and vigoritas paddy seeds. A dose irradiasi gamma rays 500 Gy cause the lowest of viabilitas and vigoritas seed of all treatment.Keyword: Irradiation gamma rays, doses, viability, vigority, seed.